Implementasi Fungsi Manajemen Dakwah untuk Pembentukan Akhlaqul Karimah Santri Pesantren di Medan - Salshabila, Jihan; Surya , Maulana Andi (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2025)
Management functions such as planning, organizing, implementing and evaluating are implemented in structured daily programs to strengthen institutions based on qismul, as well as personal development based on values. The purpose of this study is to describe and examine how planning, organizing, implementing and evaluating the functions of da'wah management are used to improve students' Akhlak standards at the Al-Kautsar Al-Akbar Islamic Boarding School in Medan. The Akhlak dilemma faced by students as a result of the increasing impact of digital media and globalization, which requires the use of organized da'wah management strategies that focus on character development. The research method used in this study is the Qualitative Method where interviews are used as data collection and assisted by documentation studies. The results of the study show how the four functions of da'wah management have been applied methodically in the form of worship practices, daily Akhlak development programs, neat Islamic boarding school organizational structures, and individual student evaluations based on a humanistic framework. This study shows that the da'wah management functions that are applied systematically are effective in improving the Akhlaks of students. This approach is a strategic solution in answering the Akhlak challenges of students in the digital era through targeted and humanistic character development.